Biosynthesis of Silver Nanoparticles Using Kedrostis foetidissima (Jacq.) Cogn. - M. Amutha; P. Lalitha; M. Jannathul Firdhouse (Journal of Nanotechnology)
Nanosilver was synthesized using the aqueous solution of solvent extracts of leaf and stem of Kedrostis foetidissima. Three different methods of formation of silver nanoparticles such as reaction at (i) room temperature, (ii) higher temperature, and (iii) sonication were employed in the present study. The synthesized silver nanoparticles were characterized by UV-visible spectroscopy, X-ray diffractometer, Scherrer’s formula, scanning electron microscopy, and FTIR analysis.